Structure of rheumatic diseases among adult population of Russia according to data of an epidemiological study (preliminary results) - E A Galushko; T Y Bolshakova; I B Vinogradova; O N Ivanova; O M Lesnyak; L V Menshikova; T N Petrachkova; S F Erdes (Научно-практическая ревматология)
Preliminary results of interregional program “Social and economic consequences of rheumatic diseases” diagnostic stage are presented.Objective. Clinical examination of persons with joint pathology revealed during screening to determine the diagnosis.Material and methods. A group of persons, who had joint complaints at the examination or during the previous year, was randomly formed according to the results of screening. Thorough uniform clinical examination with participation of a qualified rheumatologist aimed to precise determination of rheumatic pathology character was performed in all cases. During screening 1755 from 2723 persons examined at diagnostic stage positively answered question about presence of joint swelling and 968 complained of pain in knee and hip joints.Results. In 1971 from 2723 persons (72,4%) different rheumatic diseases were diagnosed. Nonrheumatic pathology was revealed in 371 (13,6%), low back pain – in 218 (8%) persons. In 163 (6%) persons no disease was determined. Osteoarthritis (49%) and rheumatoid arthritis (3%) were the most frequent causes of joint complaints. Other RD were revealed in 20%.Conclusion. Preliminary results of program diagnostic stage demonstrated significance of joint pathology problem and allowed to get the first data about structure of RD among adult inhabitants of Russia.